Assessment of HER2/Neu status by fluorescence in situ hybridization in immunohistochemistry-equivocal cases of invasive ductal carcinoma and aberrant signal patterns: A study at a tertiary cancer center - Sudha S Murthy; D G Sandhya; Faiq Ahmed; K Iravathy Goud; Monal Dayal; K Suseela; Senthil J Rajappa (Wolters Kluwer Medknow Publications, 2011)
Introduction: HER-2/neu status determines the eligibility for targeted therapy with trastuzumab in breast carcinoma. Evaluation for HER-2/neu protein expression by immunohistochemistry (IHC) and gene amplification by fluorescence in situ hybridization (FISH) has become the gold standard. Aims: Since data on HER-2/neu assessment by IHC and FISH and studies regarding concordance between the results of the two techniques are limited, especially from India, we sought to study HER-2 gene amplification status by FISH in equivocal (2+) cases by IHC and also study aberrant signal patterns. Settings and Design: Mastectomies and breast core biopsies, equivocal for HER-2/neu protein expression, were analyzed for HER-2 amplification by FISH. Materials and Methods: IHC (DAKO) and FISH (PathVysion dual-probe system) tests were performed on 68 of 112 (after exclusion) 10% neutral buffered formalin (NBF)-fixed paraffin-embedded tissues and evaluated according to American Society of Clinical Oncology ASCO guidelines. Statistical Analysis Used: Chi-square (χ2 ) test and the two-tailed P value were applied using Graphpad Quickcels software, version 2006. Results: It was found that 73.5% of the IHC 2+ patients were negative for HER-2/neu amplification, 25% were positive (ratios ranging from 2.3 to 5.6) and 1 patient was equivocal (2.2). Retesting FISH HER-2 equivocal case on another tumor block by IHC demonstrated HER-2 overexpression of protein 3+, thus resolving the equivocal status. Polysomy and HER-2 genetic heterogeneity were seen frequently. Conclusions: The findings reiterate that IHC HER-2 equivocal cases are a heterogenous group and need FISH for further categorization. Low concurrence (25%) rate between both IHC and FISH results in the equivocal scenario can be attributed to tumors with polysomy 17 and HER-2/neu genetic heterogeneity.